A Curse of Cattle? Ranching and Land Concentration in Buenos Aires During the First Globalization - Droller, F (LSE Press, 2025)
Argentina experienced notably greater land concentration than other frontier economies during the First Globalization, a disparity with lasting political and economic consequences. While existing scholarship emphasizes political explanations for this inequality, we propose a novel hypothesis: the pre-existing dominance of cattle ranching in the Pampas fostered a pattern of large landholdings that persisted even after agricultural expansion. Unlike North America, where agriculture advanced into territories previously roamed by buffalo, Argentina’s ranching legacy created a structural barrier to more egalitarian land distribution. Using census data we show that landholdings were significantly larger in counties of Buenos Aires province with a history of ranching. Our findings highlight the enduring impact of early productive specialization on long-run inequality. © 2025 The Author(s).